Relasi Sosial Masyarakat Pendatang Dengan Masyarakat Lokal di Desa Keramas, Kecamatan Blahbatuh, Kabupaten Gianyar - Pradipa, Ni Putu Nandita; Tamim, Imron Hadi; Krisna Aditya, I Gst. Ngr Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the social relations between immigrants and local communities in Keramas Village, Blahbatuh District, Gianyar Regency. Migration of people from other areas of origin within a certain period of time can cause social relations between immigrants and local communities. The theory used in this study is Structural Functionalism by Talcott Parsons, which sees society as a functionally integrated system in the form of balance. In this theory there is the AGIL Concept, namely Adaptation, Goal Attainment, Integration, and Latency. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation of immigrants and local communities in Keramas Village. The results of the study show that the relationship between immigrants and local communities in Keramas Village is harmonious without any conflict. Local communities are generally open-minded to the presence of immigrants as long as they can adapt well, obey applicable regulations, and respect local culture and social norms. Their presence creates job opportunities and increases economic activity, without causing competition that is detrimental to the local community. Social interactions between immigrants and local residents occur more in the form of daily relationships, such as greeting each other and chatting when meeting. The principle of mutual respect is the main key in building harmonious relationships, especially considering the cultural differences between them. This study concludes that the relationship between immigrants and local communities runs harmoniously by showing attitudes of mutual respect, openness, and awareness to maintain social are the main factors in creating a harmonious life. Keywords : Social Relations, Immigrant Community, Local Community, Structural Functionalism.